Idiopathic facial aseptic granuloma treated with oral doxycycline with early complete resolution. - Algarra-Sahuquillo, J.; Arteaga-Henríquez, M.; Ramírez-Conchas, J.M.; Santos-e-Silva Caldeira-Marques, M.L.; Ramos-Rodríguez, D.; Guimerá Martin-Neda, F. (European Journal of Pediatric Dermatology, 2022)
IFAG is an infrequent, exclusively pediatric disease of unknown etiology. Ages of appearance range from 8 months to 13 years old. Characteristic lesions are solitary red-violaceous papules or nodules usually located on the triangle formed by the ear lobe, labial angle, and the outer limit of the orbit. Pain or fever are typically absent, and cultures are negative. Even its etiology is still unknown. Some Authors have related its clinical appearance with the granulomatous form of infantile rosacea, although they differ in evolution (2). Diagnosis is clinical. Doppler ultrasound, when performed, shows a circumscribed solid-cystic, hypoechoic dermal lesion parallel to the skin surface, with no calcium deposits. Histopathologic findings include dermal inflammatory infiltrate forming granulomas, generally composed of lymphocytes, histiocytes, neutrophils and giant cells. Although spontaneous resolution has been reported over a one-year period (1), IFAG is a disease that tends to chronicity. The latter, in conjunction with its clinical manifestations, can generate anxiety in parents who frequently seek for treatment. Improvement with systemic antibiotics such as doxycycline, clarithromycin, ivermectin or metronidazole has been described in the literature. Topical treatment with metronidazole or ivermectin has also been proposed. However, the discussion is still open on duration and doses (3, 4). Invasive interventions such as surgical excision are not recommended as first-line therapies due to the possibility of scarring.